Prediction of Effective Bed Thermal Conductivity and Heat Transfer Coefficient in Fluidized Beds - I. Abdul-Wahab, Majid; A. Mohammed, Suha (Iraqi Journal of Chemical and Petroleum Engineering, 2009)
Experimental study of heat transfer coefficients in air-liquid-solid fluidized beds were carried out by measuring the heat rate and the overall temperature differences across the heater at different operating conditions. The experiments were carried out in Q.V.F. glass column of 0.22 m inside diameter and 2.25 m height with an axially mounted cylindrical heater of 0.0367 m diameter and 0.5 m height. The fluidizing media were water as a continuous phase and air as a dispersed phase. Low density (Ploymethyl-methacrylate, 3.17 mm size) and high density (Glass beads, 2.31 mm size) particles were used as solid phase. The bed temperature profiles were measured axially and radially in the bed for different positions. Thermocouples were connected to an interface system and these measurements were monitored by computer on line. Theoretical analysis has been carried out to solve the differential equation governing heat transfer in the gas-liquid-solid fluidized system with its boundary conditions. Finite difference technique was used as a suitable numerical method to find the solution. By applying the temperature profiles found experimentally in solved equation, effective thermal conductivity values were found.